Stabilization of the Shear Strength of Clay Soil with Limestone Powder - Widya Ayu Prawesthi; Lelita Pratiwi Santosa (International Conference on Coastal and Delta Areas, 2017)
Soil is base and the most widely material used for civil engineering and structural engineering construction. However, not all kind of soils can be used for the construction. For a soil having low a shear strength such as a soft soil, it needs to stabilize. Stabilization methods that commonly used are by compaction or chemical stabilization. With the objective to study the shear strength of clay soil, this research performed an experimental study by adding variation of limestone powder to clay soil. The clay sample is from Nganjuk city, East Java that is classified as a montmorillonite clay with Gs number is 2,698; liquid limit 62,6 %; plasticity index 19,07% , and the qu number is 1 Kg/cm2. The percentages of the limestone powder were in 5%,10%,15%,and 20%. The pure clay and modified clay were tested using Unconfined Compression Test (UCT). The result showed that with the addition of 20% limestone powder may decrease the Gs number to be 2,351; liquid limit 54,2%; and plasticity index 7,81 %; however the qu number increased with the addition 5-15% limestone powder but it decreased with 20%. Keywords: clay soil, soil stabilization, limestone, shear strength, unconfined compression test